Multiscale Analysis on the Pricing of Intensity-Based Defaultable Bonds - Sun-Hwa Cho; Jeong-Hoon Kim; Yong-Ki Ma (Journal of Applied Mathematics)
This paper studies the pricing of intensity-based defaultable bonds where the volatility of default intensity is assumed to be random and driven by two different factors varying on fast and slow time scales. Corrections to the constant intensity of default are obtained and then how these corrections influence the term structure of interest rate derivatives is shown. The results indicate that the fast scale correction produces a more significant impact on the bond price than the slow scale correction and the impact tends to increase as time to maturity increases.